Improving the Students’ Writing Skills by Using Track Changes in Paired Writing Correction - Putri Rahmayanti; I Gede Oka; I Nyoman Adi Jaya Putra (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2020)
Researchers made observations during the writing class. There were several writing problems faced by students, including: spelling errors in writing a few words, difficulty in compiling ideas, grammatical errors, incorrect punctuation, and inaccurate diction used. The researcher then found a solution to that problem by using the track changes feature in the pair correction activity. Track changes was useful for correcting students' writing in the editing phase not only making corrections, students also worked together in groups in pairs to produce better writing. The study used a classroom action research that aimed to describe the implementation of the use of track changes in pair correction activities and to find out whether the strategy could improve students' writing skills. The subjects of this study were students in class XI IPA 1 with a total of 32 students. The procedures in this study included planning, action, observation, and reflection. Researchers collected data through pre-test, post-test, questionnaire, and interview. The researcher used two cycles in this research. The results of the pre-test action showed that the average grade of the class was 67, after implementing the strategy, the average class in the first post test was 79 and in the second post-test it was 81. Based on these results, the use of track changes in writing correction in pairs could improve students' writing skills. The data were also supported by the results of questionnaires and interviews obtained that track changes helped students in learning to write.